Performance of dolomite with different percentage as sand replacement in foam concrete - Nur Hazwani, Mat Ropi (2019)
This paper investigate the performance of dolomite with different percentage as sand replacement in production of foam concrete to increase the compressive strength and reduce the uses of sand in construction while reducing river pollution. The production of foam concrete mix depend on material section, selected foaming agent and mixture design strategies. The objective of this study are observed the physical properties (shape, size, silt content) and chemical composition of dolomite and also to determine the compressive strength of foam concrete. The physical and chemical properties of the dolomite was tasted using microscope, silt test, sieve analysis, X-Ray Fluorescence (XRF), Scanning Electron Microscopy (SEM) and X-Ray Diffraction Analysis (XRD). The percentage rate of dolomite are 10%, 20%, 30% and 40% meanwhile the sample for 0% of dolomite was used as the control sample. The total of specimen are 45 cubes using form cube size 100mm x 100mm x 100mm with using dolomite that passing through 600micron sieve size and the density for 100mm3 is 1600kg/m3. Foam water ratio is 1:25. The test for determined the compressive strength of foam concrete was conducted for 7 days, 14 days and 28 days during curing processed. Results indicate that 30% of dolomite significantly improved the compressive strength of foam concrete. The obtained results are analysed and the other physical and chemical properties of dolomite are recorded.